Comparing the potential reproductive phenology between restored areas and native tropical forest fragments in Southeastern Brazil - Rother, Débora C.; de Sousa, Igor L. F. [UNESP]; Gressler, Eliana [UNESP]; Liboni, Ana P.; Souza, Vinícius C.; Rodrigues, Ricardo R.; C. Morellato, L. Patrícia [UNESP] (Wiley, 2022)
Plant phenology is rarely considered when selecting species used in restoration actions. However, considering the potential flowering and fruiting phenologies of species is a key point to: (1) evaluate the capacity of restoration actions in reestablishing ecological interactions (pollination and seed dispersal) and ecosystem functions (early germination and plant establishment to reduce soil erosion); (2) determine which species are most suitable to the target site, and (3) identify when and where locally adapted seeds can be harvested and purchased. Here, we evaluate the potential reproductive phenology of species occurring in restored and forest fragments in Southeastern Brazil. We asked whether flowering and fruiting phenological patterns differed among type areas. For such, we compared 14 restored areas and 18 nearby forest fragments and compiled phenological data from the literature for 267 species (84% of species sampled). Despite their low floristic similarity, restored and forest fragments showed close similarity of general potential flowering and fruiting periods year-round, peaking in the dry-to-rainy season. There were only slight differences in seasonality of two out of the eight parameters evaluated. Nonzoochorous species' fruiting was seasonal, while zoochorous species fruiting onset occurred year-round but was slightly seasonal in forest fragments. Comparing potential phenological patterns between restored and forest fragments using a compilation from secondary sources are unprecedented in Brazil at this scale. Our results highlight that applying phenological information, even from literature, is essential to improve the science and practice of future restoration actions, enhancing the likelihood of successful restoration of ecosystem functions and species interactions.
Keywords: Atlantic forest; ecosystem services; flowering; fruiting; restoration plantings; seasonal forest; species traits